Cryogenic Microstructure Engineering of PVDF-Based Composite Membranes Doped with Alumina and Reduced Graphene Oxide Derived from Palm Kernel Shell (PKS) - Meilysa Yonara; Delovita Ginting; Romi Fadli Syahputra; Asanah Radhi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Composite polymer membranes based on polyvinylidene fluoride (PVDF) have attracted attention as potential solid-state electrolyte candidates due to their thermal stability and mechanical robustness. However, microstructural heterogeneity and transport limitations remain key challenges. This study investigates the effect of cryogenic treatment (Series A) and rGO incorporation (Series B) on PVDF/Al2O3/CA composite membranes derived from palm kernel shell (PKS)-based reduced graphene oxide (rGO). Morphological characterization showed a reduction in pore size from 13–15 μm in the untreated membrane to 1.7–2.6 μm in the 2-minute treatment, improving membrane uniformity. UV–Vis spectroscopy revealed an increase in apparent optical band gap from 1.34 eV to 1.44 eV with increasing cryogenic duration, suggesting improved structural ordering within the composite membrane. Cyclic voltammetry (CV) measurements conducted under aqueous Na2SO4 conditions showed increased current response and capacitance with increasing rGO content (Series B), indicating enhanced interfacial electrochemical behavior. Electrochemical impedance spectroscopy (EIS) performed on Series A samples demonstrated a decrease in area-specific bulk resistance from 0.14 to 0.10 Ω·cm2, corresponding to an apparent ionic conductivity of 8.0 × 10−2 S/cm under the applied aqueous screening configuration. The results indicate that cryogenic treatment primarily governs bulk resistance reduction through pore refinement, while rGO incorporation enhances electrochemical response under model aqueous conditions. These findings highlight the role of structural control and biomass-derived carbon fillers in tailoring composite membrane electrochemical characteristics.